1997
DOI: 10.1177/107815529700300103
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of a flush solution of heparin, vancomycin, and colistin for implantable access systems in oncology

Abstract: Introduction: Because of the increased use of im plantable access systems, the incidence of blood stream and catheter infections associated with these systems has concomitantly increased. Classically, he parin-lock flush solutions were used to prevent thrombosis; more recently, vancomycin was added to the solution to prevent infections caused by Gram- positive bacteria, particularly coagulase-negative Staphylococci. Disorders due to Gram-negative organ isms have now appeared in oncologic patients. We therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…58 When vancomycin 0.1 mg/ mL was combined with colistimethate sodium 0.1 mg/mL and heparin sodium 100 units/mL, the vancomycin concentration remained stable for 60 days at 4 °C and for 15 days at 25 °C. 63 Published reports on research into other combinations using vancomycin discuss solutions containing ceftazidime, amikacin, and rifampin, but these studies reported only on visual compatibility at varying concentrations. 19,46,64,65 These antibacterial lock solution combinations may be useful in patients with polymicrobial infections.…”
Section: Antibacterialsmentioning
confidence: 98%
See 1 more Smart Citation
“…58 When vancomycin 0.1 mg/ mL was combined with colistimethate sodium 0.1 mg/mL and heparin sodium 100 units/mL, the vancomycin concentration remained stable for 60 days at 4 °C and for 15 days at 25 °C. 63 Published reports on research into other combinations using vancomycin discuss solutions containing ceftazidime, amikacin, and rifampin, but these studies reported only on visual compatibility at varying concentrations. 19,46,64,65 These antibacterial lock solution combinations may be useful in patients with polymicrobial infections.…”
Section: Antibacterialsmentioning
confidence: 98%
“…At day 30, a 25% decrease in vancomycin concentrations was found; however, colistimethate and heparin activity remained within 10% of the initial activity. 63 Rifamycins. Rifampin used synergistically with other antimicrobials for ALT displays potent elimination of biofilm and prevention of the occurrence of resistant organisms, but validated stability data are lacking.…”
Section: Antibacterialsmentioning
confidence: 99%
“…Stability data for colistimethate and SMX/TMP are limited, but these may be potential options for treatment of CRBSI secondary to MDRO. 46 Clindamycin use in a lock solution is limited to a single published study. 26 Macrolides have been utilized in lock solutions in combination due to their potential impact on biofilms.…”
Section: Antibiotic Lock Solutionsmentioning
confidence: 99%